Corn (Zea mays) Based Nutri-Powder Soup Noodles - Lazo, Angelica; Peñalber, Martina (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and evaluated Corn (Zea mays)-Based Nutri-Powder Soup Noodles as a potential functional food product aimed at enhancing nutrition and promoting food innovation. The purpose of the study was to formulate and test Corn (Zea mays)-based Nutri-Powder Soup Noodles with respect to nutritional composition, sensory acceptability, shelf life and cost effectiveness. Five formulations were made; a control (F0) and four formulations (F1-F4) with different amounts of corn-based nutri-powder. The proximate analysis showed that there were significant differences (p < 0.05) among formulations whereby corn nutri-powder levels increased to higher levels leading to high protein, fiber, ash, lipid content and metabolized energy, and a decrease in carbohydrate content. There was a slight increase in moisture content, which can have an impact on product shelf stability. The hedonic assessment based on a 9-point scale revealed that F1 and F2 scored the highest in color, aroma, taste, firmness, and overall acceptability as Like extremely. Conversely, F3 and F4 were less acceptable because of over substitution. The Acceptability Composite Index was able to determine that F1 was the most desirable formulation. The results of shelf-life proved that all the formulations were acceptable within two days and spoilage was evident after Day 3. Cost analysis revealed that the increase in production costs was associated with increasing levels of Corn Nutri-Powder. As F0 was most profitable, F1 offered the most suitable ratio between cost, nutrition, and acceptability, making it the most feasible to commercialize.
Keywords: Corn (Zea mays); Nutri-Powder Soup Noodles; Functional Food; Nutritional Fortification; Sensory Evaluation; Product Development